Determination of amygdalin content in peach oil obtained by pressing method - Madaminova, Zilola; Khamdamov, Anvar; Xudayberdiyev, Absalom (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The aim of this study is to determine the amygdalin content in peach oil obtained using the pressing method. This information is crucial for evaluating the quality of peach oil and expanding its potential applications in pharmacological and food industries. Additionally, the study examines the effect of the pressing process on the amygdalin content, providing a significant scientific basis for optimizing peach oil production processes in the future.